What risks do herbal products pose to the Australian community?. Issue 2 (6th February 2017) - Byard, Roger W; Musgrave, Ian; Maker, Garth; Bunce, Michael
Abstract: Traditional herbal products are widely used in Australia to treat a broad range of conditions and diseases. It is popularly believed that these products are safer than prescribed drugs. While many may be safe, it is worrying that the specific effects and harmful interactions of a number of their components with prescription medications is not well understood. Some traditional herbal preparations contain heavy metals and toxic chemicals, as well as naturally occurring organic toxins. The effects of these substances can be dire, including acute hepatic and renal failure, exacerbation of pre‐existing conditions and diseases, and even death. The content and quality of herbal preparations are not tightly controlled, with some ingredients either not listed or their concentrations recorded inaccurately on websites or labels. Herbal products may also include illegal ingredients, such as ephedra, Asarum europaeum (European wild ginger) and endangered animal species (eg, snow leopard). An additional problem is augmentation with prescription medications to enhance the apparent effectiveness of a preparation. Toxic substances may also be deliberately or inadvertently added: less expensive, more harmful plants may be substituted for more expensive ingredients, and processing may not be adequate. The lack of regulation and monitoring of traditional herbal preparations in Australia and other Western countries means that their contribution to illness and death is unknown. We need to raise awareness of these problems with health care practitioners and with the general public.